Study of aqueous blends of (2-(methylamino)ethanol+aminoethylethanolamine) and (2-(ethylamino)ethanol+aminoehtylethanolamine) for post-combustion co2 capture - Pandey, Diwakar (IIT (BHU), Varanasi, 2021)
Greenhouse gases are the main cause of global warming. Carbon dioxide (CO2) contributes to a major fraction of greenhouse gases. CO2 emitted into the atmosphere by the combustion of fossil fuels during industrial activities. CO2 capture from the flue gases is important due to environmental concern. The post-combustion absorption technique is most matured and useful for CO2 capture containing low partial pressure CO2. The aqueous monoethanolamine (MEA)) has been shown good CO2 absorption capability with fast reaction kinetics and considered as an industrial benchmark solution for CO2 absorption. But its high heat of CO2 absorption is a major drawback because of the high energy requirement for regeneration of CO2-loaded solution. In order to minimize demerits and utilize the advantages of individual single amines, amine blends are used. However, it is still a matter of research to find out a solvent that has high CO2 solubility, a faster CO2 absorption-desorption rate, and low heat of absorption as well. 2-(methylamino)ethanol (MAE) and 2-(ethylamino)ethanol (EAE) produce less stable carbamate, with fast reaction kinetics towards CO2, have better favorable properties of CO2 absorption, and reported as a better alternative to MEA in the literature. Aminoethylethanolamine (AEEA) is a di-amine containing one primary and one secondary amine. Its absorption capacity and absorption rate are high. AEEA was used as an activator for secondary and tertiary amines in the literature. So, the research objectives were decided to study of aqueous MAE + AEEA and aqueous EAE + AEEA blend for post-combustion CO2 capture. The complete research work of this thesis can be summarized in different chapters as follows: Chapter 1 explains the CO2 emission scenario and its consequences on the environment based on fossil-fuel combustion. Various technologies and techniques for Preface xxiii CO2 capture are discussed. Post-combustion CO2 capture using chemical absorption technique based on the amine solvents are described. Literature reviews related to CO2 absorption into MAE, EAE, and AEEA are given in detail. Literature reviews about CO2 solubility models and physicochemical properties of amine absorbents are also depicted briefly. The literature gaps have been identified and included in this chapter. The objectives of the present work also have been provided in this chapter. Chapter 2 describes CO2 solubility data of aqueous (MAE + AEEA) blend at different operating conditions. Modified Kent-Eisenberg (K-E) thermodynamic model has been given for CO2 solubility in aqueous (MAE + AEEA) blend. Determination of heat of CO2 absorption for aqueous (MAE + AEEA) blend using CO2 solubility data has also been provided. Chapter 3 explains experimental CO2 solubility measurement and modified K-E model for aqueous (EAE + AEEA) blend. The development of an empirical model for CO2 solubility prediction has been also shown. The heat of CO2 absorption for the aqueous (EAE + AEEA) blend has been discussed based on Gibbs-Helmholtz equation. The initial rate of change of CO2 solubility with respect to time during absorption as well as desorption has been discussed. Cyclic capacity of aqueous (EAE + AEEA) blend and its comparison with cyclic capacity of aqueous monoethanolamine (MEA) are discussed. Chapter 4 describes the viscosity and density of EAE + H2O, AEEA + H2O, and EAE + AEEA + H2O. Excess molar volume has been calculated for mixtures in the range of 293.15 K to 333.15 K and correlated to the Redlich-Kister model. Experimental viscosity and density data have been correlated to the newly developed empirical models. In order to extend the knowledge of molecular interaction, derived thermodynamic properties have been studied. Preface xxiv Chapter 5 illustrates the density and viscosity of the CO2-loaded and –unloaded aqueous (EAE+AEEA) blend. Excess volume has been calculated in the temperature range of 293.15 to 323.15 K for –unloaded aqueous (EAE+AEEA) blend and fitted to the newly developed empirical model. Newly proposed empirical correlations have been given to predict the density and viscosity of the CO2-loaded and –unloaded aqueous (EAE+AEEA) blend. CO2 diffusivity into the aqueous EAE+AEEA blend has been discussed. Chapter 6 contains the overall conclusions of this research work and recommendations for future work. On the basis of this research work, it has been concluded that the aqueous (EAE+AEEA) blend has a good potential for post-combustion CO2 absorption.
Acc.No-954
Keywords: Aqueous Blends; Methylamino; Post-Combustion Co2; Aminoethylethanolamine